Chemical and biological activity studies of Averrhoa carambola L. - Sharmin Shahjahan; Mohammad Shoeb; Md. Mazharul Islam; Md. Iqbal Rouf Mamun; Md. Nazrul Islam (Current Research on Bioscences and Biotechnology, 2023)
Averrhoa carambola L., belonging to the Oxalidaceae family is one of the popular fruits in Bangladesh. The objective of the study is to isolate and purify secondary metabolites from A. carambola leaves and investigate phytochemical properties, fatty acid, antioxidant, antimicrobial activity, and cytotoxicity in both fruits and leaves. Phytochemical screening revealed the presence of lignins, quinones, saponins, flavonoids, phenol, carbohydrates, steroids, and terpenoids. Repeated column chromatography of the dichloromethane (DCM) extract of leaves yielded three compounds: β-sitosterol, 6,9-dieneoctadeca-1-ol, and palmitic acid, characterized using spectroscopic techniques. The n-hexane extract of the fruit showed the presence of palmitoleic acid (20.94%) and octadecanoic acid (48.48%), while palmitoleic acid (6.47%), octadecanoic acid (23.23%), and behenic acid (41.70%) predominated in the leaves. For DPPH free radical scavenging activity, the IC50 value of methanol (MeOH) extracts was found to be 16.71 and 27.30 µg/mL in fruits and leaves, respectively, which is lower than that of n-hexane (IC50 value 282.46 and 78.65 µg/mL in fruits and leaves, respectively) and DCM (IC50 value 32.98 and 39.38 µg/mL in fruits and leaves, respectively) extracts. None of the extracts showed significant antibacterial or antifungal activities. Cytotoxicity assay was performed on HeLa and Vero cell lines, and only the DCM extract of fruits exhibited cytotoxicity on the Vero cell line.